Not moving: the fundamental but neglected motor function - Noorani, Imran (Philos Trans R Soc Lond B Biol Sci, 2017)
The function of the motor system in preventing rather than initiating movement is often overlooked. Not only are its highest levels predominantly, and tonically, inhibitory, but in general behaviour it is often intermittent, characterized by relatively short periods of activity separated by longer periods of stillness: for most of the time we are not moving, but stationary. Furthermore, these periods of immobility are not a matter of inhibition and relaxation, but require us to expend almost as much energy as when we move, and they make just as many demands on the central nervous system in controlling their performance. The mechanisms that stop movement and maintain immobility have been a greatly neglected area of the study of the brain. This paper introduces the topics to be examined in this special issue of Philosophical Transactions, discussing the various types of stopping and stillness, the problems that they impose on the motor system, the kinds of neural mechanism that underlie them and how they can go wrong. This article is part of the themed issue ‘Movement suppression: brain mechanisms for stopping and stillness’.